THE ROLE OF SOCIAL SUPPORT IN REDUCING ANXIETYFACING THE FUTURE FOR GEN-Z IN THE DIGITAL ERA TANJUNG BALAI - Jibril, Ahmad; Metia, Cut (MSJ : Majority Science Journal, 2025)
This study aims to examine the role of social support in reducing anxiety levels experienced by Generation Z in facing the future in the digital era of Tanjungbalai. Generation Z is the generation born between 1997 and 2012. Generation Z lives amidst the rapid development of digital technology that brings unique challenges, including economic uncertainty, social pressure, and fear of the future. Through a qualitative approach, this study used observation and interview methods with five informants from Tanjungbalai City. The results showed that Generation Z anxiety was triggered by academic pressure, social comparison, and global uncertainty related to the economy and the environment. Social media shows a dualistic impact on the one hand exacerbating anxiety through exposure to unrealistic standards of success and negative content, but on the other hand serves as a source of career information, inspiration, and the formation of a supportive community. In this context, social support, especially emotional support empathy, validation of feelings and instrumental concrete assistance, practical solutions from close friends and family proved to be a critical coping mechanism. Its effectiveness depends on the quality of the interaction, where non-empathetic support can actually increase anxiety.